Semantic Processing in Deaf and Hard-of-Hearing Children: Large N400 Mismatch Effects in Brain Responses, Despite Poor Semantic Ability - Kallioinen, Petter; Olofsson, Jonas; Nakeva von Mentzer, Cecilia; Lindgren, Magnus; Ors, Marianne; Sahlén, Birgitta S.; Lyxell, Björn; Engström, Elisabet; Uhlén, Inger (Frontiers in Psychology, 2016)
Difficulties in auditory and phonological processing affect semantic processing in speech comprehension of deaf and hard-of-hearing (DHH) children. However, little is known about brain responses of semantic processing in this group. We investigated event-related potentials (ERPs) in DHH children with cochlear implants (CI) and/or hearing aids (HA), and in normally hearing controls (NH). We used a semantic priming task with spoken word primes followed by picture targets. In both DHH children and controls, response differences between matching and mismatching targets revealed a typical N400-effect associated with semantic processing. Children with CI had the largest mismatch response despite poor semantic abilities overall, children with CI also had the largest ERP differentiation between mismatch types, with small effects of within-category mismatches (target from same category as prime) and large effects between-category mismatches (were target is from a different category than prime). NH and HA children had similar responses to both mismatch types. While the large and differentiated ERP responses in the CI group were unexpected and should be interpreted with caution, the results could reflect less precision in semantic processing among children with CI, or a stronger reliance on predictive processing.